2011
DOI: 10.1128/aac.01627-10
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Characterization of Naturally Occurring Polyketide Cyclophilin Inhibitors from the Sanglifehrin Family

Abstract: Cyclophilin inhibitors currently in clinical trials for hepatitis C virus (HCV) are all analogues of cyclosporine (CsA). Sanglifehrins are a group of naturally occurring cyclophilin binding polyketides that are structurally distinct from the cyclosporines and are produced by a microorganism amenable to biosynthetic engineering for lead optimization and large-scale production by fermentation. Preclinical characterization of the potential utility of this class of compounds for the treatment of HCV revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 48 publications
1
47
0
2
Order By: Relevance
“…We first found that alisporivir profoundly blocks wild-type Con1 replication (Fig. 2D), confirming that this Cyp inhibitor efficiently inhibits HCV replication in vitro (6,11,18,19,25,26,33,37,39,44,55). Importantly, the D320E or Y321N mutation alone confers only a slight resistance to the Cyp inhibitor, with the Y321N mutation having a more profound resistance impact (Fig.…”
Section: Selection Of Alisporivir-resistant Repliconsmentioning
confidence: 67%
See 1 more Smart Citation
“…We first found that alisporivir profoundly blocks wild-type Con1 replication (Fig. 2D), confirming that this Cyp inhibitor efficiently inhibits HCV replication in vitro (6,11,18,19,25,26,33,37,39,44,55). Importantly, the D320E or Y321N mutation alone confers only a slight resistance to the Cyp inhibitor, with the Y321N mutation having a more profound resistance impact (Fig.…”
Section: Selection Of Alisporivir-resistant Repliconsmentioning
confidence: 67%
“…We and others showed that CypA, via its isomerase pocket, directly binds NS5A (4,10,22,28,32). We and others also showed that Cyp inhibitors, including CsA, alisporivir, sanglifehrins, and sangamides, totally disrupt NS5A-CypA interactions (5,6,10,14,19,22,54,57). Thus, one possibility explaining how D320E and Y321N mutations render HCV resistant to alisporivir is that the mutations render NS5A-CypA interactions resistant to the drug-mediated dissociation.…”
Section: Selection Of Alisporivir-resistant Repliconsmentioning
confidence: 99%
“…These data suggest that the D320E and Y321N mutations confer low-level resistance of HCV (Con1) to Cyp inhibitors, possibly by reducing the need for CypA-dependent isomerization of NS5A. It will be interesting to determine whether the D320E and Y321N mutations confer "universal" cross-resistance among Cyp inhibitors, including SCY-635, NIM811, alisporivir, CsA, sanglifehrins A to D, and sangamides (amide derivatives of sanglifehrin A) (19). It is important to note that the RNA binding of domain II of NS5A containing the D320E mutation was unaffected by CypA (14).…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm the involvement of the MPT, we studied the effect of the MPT inhibitor SfA on mitochondrial morphology and function in these cells. We preferred SfA to the more commonly used cyclosporin A because SfA was shown to be more specific and less immunosuppressive (32). We treated LM7 and 143B cells with SfA for various times (data not shown) and found that a 7-day incubation produced the most stable effects.…”
Section: Mitochondrial Dysfunction and The Warburg Effect Arementioning
confidence: 99%